International Donor Agencies Developmental Prospects in Delta and Edo States: Conceptual Review - Michael Enahoro (Prosperity: Journal of Society and Empowerment, 2023)
The study examined the developmental prospects of international donor agencies in Delta and Edo states. Since the colonial era, some policies and programs within national development plans have been formulated to address the region's peculiarities; minority status, agitations, and perceived marginalization of the people of the Niger Delta. The study adopted the Integrated Development theoretical framework to explain the role of the selected international donor agencies in the Development of Delta and Edo States. This study adopts a qualitative research design; the researcher used descriptive analysis to examine international donor agencies' developmental prospects in Delta and Edo states. The theoretical research draws its argument from secondary data, which include journal articles, books, and internet sources, and was content analyzed about the scope of the study. The study concluded that corruption and bad governance, political and ethnic interest in developmental projects, climatic factors, poor infrastructural foundations, and expanding insecurity as critical developmental challenges affecting the survival of projects and programs in the oil-producing states.